The behavioral economics of climate change : adaptation behaviors, global public goods, breakthrough technologies, and policy-making - Seo, Sungno Niggol (Academic Press, an imprint of Elsevier, 2017)
The Behavioral Economics of Climate Change: Adaptation Behaviors, Global Public Goods, Breakthrough Technologies, and Policy-Making shows readers how to understand mitigation strategies emerging from global warming policy discussions and the ways that changing climate conditions can alter these strategies. Through quantitative analyses, case studies and policy examples, this bottom-up approach to climate change economics gives readers the tools to create effective responses to global warming. This self-contained book on the topic covers key scientific and economic subjects in an applied, innovative and immediately relevant fashion.